A problem-focused approach to violence against women: The political-ec onomy of justice and security programming - Denney, Lisa; Domingo, Pilar (ODI, 2013)
The United Nations Commission on the Status of Women ended its 57th se ssion on 15 March 2013 with an outcome document affirming the importan ce of eliminating violence against women (VAW). The Commission was una ble, however, to achieve consensus on a global action plan. The negati ve reaction of some UN member states to an action plan is a worrying r eminder of ongoing resistance to reform. These persistent challenges h ighlight the continuing struggle to gain a serious global commitment t o address VAW and recognise it as a breach of women’s fundamental huma n rights. Engaging in this struggle, many donors have put addressing V AW generally, and in fragile and conflictaffected situations (FCAS) sp ecifically, at the top of the development agenda and made it a major p riority of international policy. But in practice progress remains diff icult, not least due to entrenched resistance and discriminatory socio -political norms and gender relations that persist in many societies. The problem of violence against women therefore needs to be addressed from the perspective of the concrete socio-political and cultural cond itions that shape its particular features and the relevant context spe cific dynamics of conflict, post-conflict patterns of violence and fra gility. International efforts to support reform in the area of VAW in FCAS need to go beyond prescriptive approaches that focus on what acce ss to protection, justice and redress should look like. We propose her e an approach that engages with the specificities of the problem – pay ing attention to context, and the concrete political-economy dynamics of the drivers of VAW – and takes account of the real options that